Pelatihan Merek Dan Packaging Pada Usaha Jajanan Tradisional Di Desa Langko Kecamatan Lingsar. - Sriningsih, Siti; Fatimah, Siti; Arini, Gusti Ayu; Wijimulawiani, Baiq Saripta; Suriadi, Irwan (Universitas Mataram, 2023)
The aim of this program is to assist partners in understanding the procedures, mechanisms and processes for proposing a brand and its attributes on a traditional food product so that it looks better, the product is easy for consumers to remember and attractive to consumers. The specific target of the PPM Partnership program is the implementation of procedures and mechanisms for submitting brands and their attributes so that a product is easily remembered by consumers and turns traditional snack products into products that are well packaged and attractive and have good durability for these traditional snack products. The method used in achieving the objectives of this activity is to conduct training and mentoring procedures, mechanisms for proposing brands and their attributes as well as training in carrying out good and attractive packaging with strong and non-perishable packaging. The activities of the PPM Partnership program consist of: (1) training on procedures, mechanisms for applying for brands with IPR (2) Good packaging training starting from the selection of packaging materials such as PE food plastic wrap, packaging gluing so that traditional food products are stronger and not easily damaged. damaged. The result of this community service activity is the understanding of traditional snack entrepreneurs in Langko Village, Lingsar sub-district regarding procedures, mechanisms for branding, packaging and packaging so that traditional snack entrepreneurs can implement brand and packaging management for the sustainability of their business.